Current Status of Cardiac Rehabilitation in the Regional Cardiocerebrovascular Centers in Korea - Chul Kim (MDPI AG, 2021)
Regional Cardiocerebrovascular Centers (RCCs)—a Korean government initiative—seek to reduce medical gaps across regions, and their cardiac rehabilitation (CR) programs are expected to model post-acute care for the Korean CR program. Accordingly, this study aimed to evaluate the current status of CR programs in the RCCs. We distributed surveys on the CR condition, activity, and barriers to 12 RCCs in different provinces. The results revealed significant gaps in the annual number of acute myocardial infarction admissions, and CR candidates, capacity, and density across the 12 RCCs. The CR capacity (50–500) and density (0.42–7.36) indicated particularly large gaps. Twelve RCCs had the necessary facilities, equipment and personnel for CR assessments and management, with high CR referral (97%) and patient education (78%) rates. However, the inpatient CR exercise training (56%) participation rate was inadequate, with much lower enrollment (47%) and adherence (17%) rates to the outpatient CR program and large differences across centers. Therefore, this study’s results will provide the evidence required to establish special national health strategies to overcome the CR barriers of patient, doctor/hospital, and policy factors for activating Korean CR programs.